Впровадження методики оцінювання якості вебсайту - Гасан, О. О.; Козлов, Ю. В. (ХНУРЕ, 2025)
Before starting development, a QA engineer establishes software quality requirements. And the process of quality assurance includes the development, creation and release of software with the least number of defects and errors for the end user. QA provides such methods and techniques for all participants in the process to produce the best product at the end. As part of the research, the Prom and Rozetka sites will be tested using various methods and tools.
Keywords: оцінювання якості вебсайту; якість вебсайту